2015
DOI: 10.1007/s13277-015-3483-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142-3p inhibits cell proliferation and invasion of cervical cancer cells by targeting FZD7

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs that play important roles in tumorigenesis and tumor progression through regulation of gene expression. Earlier, miR-142-3p was shown to decreased in cervical cancer cells; here; we explore the biological functional role of miR-142-3p and underlying mechanism in cervical cancer cells. We first detected the expression of miR-142-3p in six human cervical cancer cell lines and chose HeLa and SiHa cells for functional studies. By gain and loss of function expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…Recently some studies have reported the role of miRNAs in modulating invasion and metastasis of cervical cancer cells. For instance, Deng et al (20) discovered that miRNA-142-3p restrained cervical cancer cells proliferation and invasion, indicating a potential therapeutic approach for cervical cancer (20). Another study revealed that miR-3156-3p is reduced in cervical cancer, suggesting as a tumor-suppressive miRNA (21).…”
Section: Discussionmentioning
confidence: 99%
“…Recently some studies have reported the role of miRNAs in modulating invasion and metastasis of cervical cancer cells. For instance, Deng et al (20) discovered that miRNA-142-3p restrained cervical cancer cells proliferation and invasion, indicating a potential therapeutic approach for cervical cancer (20). Another study revealed that miR-3156-3p is reduced in cervical cancer, suggesting as a tumor-suppressive miRNA (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, downregulation of miR-142-3p was observed in a large number of follicular thyroid adenomas and carcinomas, and miR-142-3p was also reported to function as a tumor suppressor in follicular thyroid tumorigenesis (16). miR-142-3p has also been reported to be able to inhibit the proliferation and invasion of cervical cancer cells by targeting frizzled-7 (30). Furthermore, lower miR-142-3p expression in hepatic cancer was associated with poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that aberrant expression of miRNAs plays pivotal roles in the development and progression of cancer by inhibiting the expression of their target genes and potentially serve as biomarkers for the prediction and prognosis in diverse cancers, including CC (26)(27)(28). In previous studies, Zhu et al demonstrated that miR-106a targets TIMP2 to regulate the invasion and metastasis of gastric cancer (15).…”
Section: Discussionmentioning
confidence: 99%